Between two rivers : ancient Mesopotamia and the birth of history - Al-Rashid, Moudhy N. (Moudhy Nasser), 1982- (W.W. Norton and Company, 2025)
"Thousands of years ago, in a part of the world we now call ancient Mesopotamia, people began writing things down for the very first time.What they left behind, in a vast region between the Tigris and Euphrates rivers, preserves leaps in human ingenuity, like the earliest depiction of a wheel and the first approximation of pi.... the world's first cities, the first writing system, early seeds of agriculture, and groundbreaking developments in medicine and astronomy"--